Circular route to the management of solid waste: A case study of EcoSage Enviro. (2022) - Shyam, Hari Shankar; Gupta, Manisha; Gupta, Himani
Abstract: These days, circular supply chain management has taken on a new level of meaning as environmental practises are incorporated into diverse supply chains. Environmental issues have gained increased importance within supply chain management, and it is necessary that each step in the supply chain management process be integrated with environmental consciousness. Solid waste management firms like EcoSage Enviro and others that include circularity in their services are inspiring interest, adoption, and replication of circular supply chain in waste management. ECOSAGE ENVIRO Waste Initiative's circular supply chain concept and its services related to waste management are good models for private–public-partnerships to follow when it comes to waste management in Himalayan region of country India.